Reorienting the Sasanians east Iran in late Antiquity - Rezakhani, Khodadad 1967- (Edinburgh studies in ancient Persia, 2017)
The Sasanians were the last great power to rule over Iran/Persia before the advent of Islam. Through the use of archaeological material, coins, artistic remains, as well as primary sources in the local languages of Central Asia, Rezakhani will look at the world of the east as it was viewed by the Sasanians and evaluate their presence in the lands that became Khorasan in the early Islamic period and as such a source of power struggle, change and challenge for the Islamic state